Exploring the chemotherapeutic potential of currently used kinase inhibitors: An update - Naik, Rajashri R.; Shakya, Ashok K. (Frontiers in Pharmacology, 2023)
Protein kinases are enzymes that transfer phosphate to protein, resulting in the modification of the protein. The human genome encodes approximately 538 kinases. Kinases play a role in maintaining a number of cellular processes, including control of the cell cycle, metabolism, survival, and differentiation. Protein kinase dysregulation causes several diseases, and it has been shown that numerous kinases are deregulated in cancer. The oncogenic potential of these kinases is increased by a number of processes, including overexpression, relocation, fusion point mutations, and the disruption of upstream signaling. Understanding of the mechanism or role played by kinases has led to the development of a large number of kinase inhibitors with promising clinical benefits. In this review, we discuss FDA-approved kinase inhibitors and their mechanism, clinical benefits, and side effects, as well as the challenges of overcoming some of their side effects and future prospects for new kinase inhibitor discovery.